Digital Transformation Moderates Liquidity and Operational Efficiency Effects on Banking Stock Performance in Indonesia - Rendi Syahlendra; Idham Lakoni; Melvi Yansi (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the moderating role of digital transformation on the effect of liquidity and operational efficiency on bank stock performance. Methodology: A quantitative approach using panel data regression (Random Effect Model) and Moderated Regression Analysis was applied to 110 observations from 22 conventional banks listed on the Indonesia Stock Exchange (2020–2024). Results: Liquidity negatively and significantly affects stock performance, whereas operational efficiency has an insignificant negative effect. Digital transformation significantly amplifies liquidity's negative impact but does not moderate operational efficiency. Findings: Investors tolerate short-term operational inefficiencies as necessary digital investments but penalize forced digital expansion during tight liquidity due to heightened fundamental risks. Originality/Novelty: By integrating Signaling Theory, this research introduces digital transformation as a moderator to resolve empirical inconsistencies, demonstrating that market appreciation of a bank's digital capabilities relies heavily on its fundamental liquidity. Conclusion: Massive digital investments alongside high loan-to-deposit ratios create a market-penalized double burden. Banks must balance technological expansion with liquidity stability. Type of Paper: Research Article.